Implementation and Operational Challenges of the SP4N-LAPOR Digital Complaint System: Implementasi dan Tantangan Operasional Sistem Pengaduan Digital SP4N-LAPOR - Anna Asriniati Harahap; Nursyafniati Nursyafniati (Academia Open, 2026)
General Background The integration of digital information technology into government services represents a fundamental strategy for achieving transparent and responsive public administration. Specific Background Pekanbaru City utilizes the SP4N-LAPOR application as an online platform to facilitate community participation and address service grievances. Knowledge Gap Despite an initial increase in reporting, the platform frequently encounters technical and operational barriers, necessitating a comprehensive evaluation of its actual utility and systemic constraints based on multidimensional parameters. Aims This study analyzes the operational utility of the SP4N-LAPOR application in managing public grievances at the Pekanbaru City Communications and Informatics Office, while identifying specific institutional obstacles and resolution strategies. Results Utilizing Gibson and Steers’ theoretical framework, qualitative analysis indicates that the application successfully standardized grievance procedures according to national protocols and increased overall community participation. However, systemic software errors, severe human resource shortages, and low public awareness prevent optimal service delivery. Novelty This research specifically isolates the multidimensional constraints of digital governance mechanisms within a regional Indonesian context, linking administrative personnel deficits directly to software operational delays. Implications Achieving transparent and accountable digital governance requires policymakers to prioritize technical system refinement, expand administrative personnel capacity, and conduct extensive community socialization campaigns. Highlights The integrated online platform successfully standardized public grievance procedures and increased community participation. Systemic software errors and limited administrative personnel significantly restricted optimal service delivery. Extensive community socialization remains essential to overcome awareness barriers and achieve accountable governance. Keywords Accountable Governance; Administrative Personnel; Digital Platform; Public Grievances; Systemic Barriers